Influence of Carbon Nano Tube on Dielectric Behaviour of Poly (Vinylidene Fluoride) Composite Films - Arora, Vajinder Singh (My University, 2007)
The state-of-the-art properties of PVDF-MWCNT materials have been reviewed in the context of their structural, electrical, and dielectric properties. The novel idea of nano dispersion to make nano-composite has been discussed and future directions investigated. PVDF-MWCNT composites are widely used in sensor, transducer and actuator application. In Comparison to pure PVDF or CNT materials, they have an advantage of mechanical flexibility. In this research work, an attempt way made to understand the processing and characterization of PVDF-MWCNT nanocomposites and to determine the changes in the PVDF morphology and other material parameters. In addition PVDFMWCNT composites show a linear increase in the percentage of crystallinity with the increase of MWCNT concentration in the composite. Dielectric spectroscopy results indicate that by increasing the MWCNT concentration in the composite, the dielectric constant and the polymer conductivity increase.
M.Tech. (Material Science and Engineering)
Keywords: Nano Tube, Dielectric